Pandangan Al-Qur’an Dan Hadist Terhadap Etos Kerja - Nurdin, Fauziah (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2020)
Alquran and Hadits are Islamic teachings in which there are teachings for charity and work which are recited in the sentence "amal as shalihat". Work ethic is one of the elements among the seven universal cultural elements, namely the element of "livelihood systems". livelihood system means economy. Work is an activity carried out by humans in achieving a welfare of life and if they are lazy they will fail to get it. Success and failure are the result of their own hard work. In Islam the characteristics of the work ethic of seeking the world's wealth in a lawful way, not asking for money, fulfilling family needs and compassion for neighbors. As the Prophet Muhammad saw work as the actualization of faith and devotion. Therefore for a Muslim to live is to work. Allah SWT in his word remember that Allah SWT will not change the fate of humans before humans change what is in him.